2017
DOI: 10.1016/j.msea.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Innovative analysis of Luders band behaviour in X80 pipeline steel

Abstract: In this study, the influence of Luders bands, which are frequently observed after the pipe coating process, is investigated. Stratified tensile test specimens, machined from different locations across the thickness of an X80 line pipe, were tested. The Luders bands were observed by using a digital image correlation (DIC) in the specimen machined from halfway across the pipe wall thickness. The specimens from the selected locations related to the Luders bands were studied and compared by means of optical micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The critical dislocation velocity v cr can be determined from Equation according to Tien et al, ie, vcr=Deff||Ebd30italicRT||b, where E bd denotes the binding enthalpy of the dislocation with hydrogen and “|b|” is the magnitude of the Burgers vector. The mean dislocation velocity in the tensile tests can be calculated from Orowan's relationship dtρmobvDb, where v D is the dislocation velocity and ρ mob is the density of mobile dislocations . Hydrogen requires at least 750 seconds to diffuse through an X80 sheet of thickness 2 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical dislocation velocity v cr can be determined from Equation according to Tien et al, ie, vcr=Deff||Ebd30italicRT||b, where E bd denotes the binding enthalpy of the dislocation with hydrogen and “|b|” is the magnitude of the Burgers vector. The mean dislocation velocity in the tensile tests can be calculated from Orowan's relationship dtρmobvDb, where v D is the dislocation velocity and ρ mob is the density of mobile dislocations . Hydrogen requires at least 750 seconds to diffuse through an X80 sheet of thickness 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…where v D is the dislocation velocity and ρ mob is the density of mobile dislocations. 51 Hydrogen requires at least 750 seconds to diffuse through an X80 sheet of thickness 2 mm. It shows that no degradation occurred during the straining of the precharged specimens.…”
Section: Effect Of Strain Rate On Hementioning
confidence: 99%
“…Strain aging of the pipe incurred during coating heating could increase the yield strength of the pipe to some degree. This, in turn, increases the yield ratio (Y/T) and possibly worsens the deformability of the pipes [6].…”
Section: Intorductionmentioning
confidence: 99%
“…It is well-known that most structural steels show obvious temperature dependent mechanical properties, such as yield stress, ductile-brittle fracture transition behavior. Previous investigations demonstrate that for some steels, the so-called Lüders plateau which is influenced by loading rate, ferrite grain size, yield stress, et al may occur in uniaxial tension test (Beardsmore et al, 2013;Dahl et al, 2018;Hallai and Kyriakides, 2013;Han et al, 2017;Liu et al, 2015;Mazière et al, 2017;Ren et al, 2015;Tsuchida et al, 2006). It has been reported that lowering testing temperature will increase the Lüders plateau length, see Fig.…”
Section: Introductionmentioning
confidence: 95%